Harmonisasi Hukum Penjatuhan Pada Pidana Kasus Pembunuhan Berencana Terhadap Justice Collaborator - Utama, Firdaus Rizky; Ravizki, Eka Nanda (Legal Spirit, 2025)
A Justice Collaborator is a perpetrator of a criminal act who cooperates with law enforcement authorities to later become a witness and provide testimony to help uncover specific criminal cases in exchange for a reduction in punishment, one of which involves premeditated murder as found in Verdict Number 798/Pid. B/2022/PN. Jkt. Sel. However, to become a Justice Collaborator, there are several conditions that need to be met. The aim of this research is to examine juridically the requirements for establishing a Justice Collaborator, as well as to analyze how the Judge's Consideration in Granting Leniency to Justice Collaborators in Verdict Number: 798/Pid. B./Jkt. Sel. The research method used in this study is the Normative Juridical method with a Conceptual Approach, Statutory Approach, and Case Approach. The results of this study show that in establishing a Justice Collaborator, several conditions must be met in accordance with the prevailing regulations, including Law No. 31 of 2014 and Supreme Court Regulation No. 4 of 2011, and judges in granting leniency to Justice Collaborators use several considerations, one of which is because the defendant becomes a Justice Collaborator and is willing to testify in court, thus shedding light on the case which was previously shrouded in confusion and misunderstanding from various parties, threatening to distort the truth and justice. The defendant's courage, honesty, and perseverance in facing various obstacles to uncovering the truth make them worthy of recognition as a Justice Collaborator and deserving of leniency.